One-step fabrication of hydrophilic lignosulfonate-decorated reduced graphene oxide to enhance the pervaporation performance of calcium alginate membranes - Saisai Li (Elsevier, 2022)
In this study, a reduced graphene oxide (rGO)@sodium lignosulfonate (NaLS) composite material was fabtricated using a one-step method and then mixed with natural polysaccharide calcium alginate (CaAlg) to prepare the rGO@NaLS/CaAlg pervaporation membrane. The appearance and physical properties of the rGO@NaLS/CaAlg membrane were characterized by scanning electron microscopy and water contact angle. The swelling performance of the membrane and its dehydration performance to organic solvents were evaluated. The results indicate that the addition of rGO@NaLS can increase the hydrophilicity of the rGO@NaLS/CaAlg membrane and reduce its degree of swelling in the ethanol solution. The membrane incorporated with 6 wt% rGO@NaLS exhibits the best pervaporation performance, and ethanol can be purified to 99.8%.